Training industrial end‐user programmers with interactive tutorials. (11th November 2022) - Ritschel, Nico; Sawant, Anand Ashok; Weintrop, David; Holmes, Reid; Bacchelli, Alberto; Garcia, Ronald; K R, Chandrika; Mandal, Avijit; Francis, Patrick; Shepherd, David C.
Abstract: Newly released robot programming tools have made it feasible for end‐users to program industrial robots by combining block‐based languages and lead‐through programming. To use these systems effectively, end‐users, who usually have limited or no programming experience, require training. To train users, tutoring systems are often used for block‐based programming—some even for lead‐through programming—but no tutorial system combines these two types of programming. We present CoBlox Interactive Tutorials (CITs), a novel tutoring approach that teaches how to use both the hardware and software components that comprise a typical end‐user robot programming environment. As users switch between the two programming styles, CITs provide them with extensive scaffolding, give users immediate feedback on missteps, and provide guidance on next steps. To evaluate CITs, we conducted a study with 79 industrial end‐users using a programming environment released by ABB Robotics that compares our approach to training with training videos, the most commonly used training in industry. This study, one of the largest to date on training professional end‐users, found that CIT‐trained users authored more correct programs in less time than video‐trained users. This shows that a tight integration of hardware and software concepts is crucial to training end‐users to program industrial robots.